2009
DOI: 10.3113/fai.2009.1005
|View full text |Cite
|
Sign up to set email alerts
|

Radiography versus Computed Tomography for Displacement Assessment in Calcaneal Fractures

Abstract: Underestimation of the amount of depression and rotation of the posterior facet fragment was seen on the coronal CT scan. We attribute this finding to the combined rotation and depression of the posterior facet which may not be measured accurately with the typical semicoronal CT orientation. While sagittal reconstructed images would show this depression better, if they are unavailable we recommend using lateral radiographs to better gauge the amount of fracture displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…In addition, as mentioned by Kurozumi et al, Böhler’s angle comprises multiple factors: anterior lateral wall, PTC, and tuber displacement: all of which are evaluated separately with CT imaging [ 13 ]. Still, in line with the existing literature, we did not produce high reliability of Böhler’s and Gissane’s angle measurements on CT [ 23 , 28 ].…”
Section: Discussionsupporting
confidence: 76%
“…In addition, as mentioned by Kurozumi et al, Böhler’s angle comprises multiple factors: anterior lateral wall, PTC, and tuber displacement: all of which are evaluated separately with CT imaging [ 13 ]. Still, in line with the existing literature, we did not produce high reliability of Böhler’s and Gissane’s angle measurements on CT [ 23 , 28 ].…”
Section: Discussionsupporting
confidence: 76%
“…5 These angles have been used to evaluate the degree of fracture displacement. 12,35 However, Schepers et al found that plain X-ray evaluation correlated poorly with the final outcome. 44 On the other hand, the use of CT scan (coronal, axial, and sagittal images as well as three-dimensional reconstruction) for a three-dimensional analysis of calcaneal fractures has become a routine practice in most hospitals during the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Co raz bar dziej po wszech ne sta ło się ba danie to mo gra fii kom pu te ro wej (TK), któ re po zwo li ło na do kład niej szą ana li zę mor fo lo gii zła ma nia, zwłasz -cza w przy pad ku zła mań sta wo wych. W chwi li obecnej jest nie od łącz nym ele men tem dia gno sty ki uła -twia ją cym wy bór me to dy le cze nia [8][9][10].…”
Section: Wstępunclassified
“…The end of the 20 th century major developments in calcaneal fracture work-up, including computed tomography (CT), which allowed for a more detailed analysis of the fracture morphology, especially in intra-articular fractures. Nowadays CT is a vital part of the diagnostic work-up, facilitating the choice of an appropriate treat ment method [8][9][10].…”
Section: Introductionmentioning
confidence: 99%